Improving Students’ Reading Comprehension through Powerpoint-Based Instruction: An Experimental Study at SMP Negeri 21 Palu - Aditya Moh. Zikri; Darmawan Darmawan; Wahyudin Wahyudin (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
Reading comprehension is a fundamental skill in language learning that enables students to understand, interpret, and engage with written texts effectively. However, many students, especially at the junior high school level, face difficulties in comprehending reading materials due to limited vocabulary, lack of motivation, and ineffective teaching methods. This research aimed to investigate whether the use of PowerPoint as a teaching aid could improve the reading comprehension skills of seventh-grade students at SMP Negeri 21 Palu. A pre-experimental design was employed in this study, involving 17 students selected through convenience sampling. The data were collected using multiple-choice and true-false tests administered before (pre-test) and after (post-test) the treatment. The statistical analysis revealed that the t-counted value exceeded the t-table value, indicating that the research hypothesis was accepted. These findings suggest that the use of PowerPoint has a positive effect on enhancing the students’ reading comprehension skills.